2002
DOI: 10.1021/bp025597w
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Properties of Flat Surfaces and Nanoparticles Derivatized with Alkylated Polyethylenimines

Abstract: We previously discovered that covalently coating glass and plastic slides with certain long poly(vinyl-N-alkylpyridinium) chains enables the resultant surfaces to kill a variety of airborne and waterborne bacteria on contact. In the present study, these findings have been extended to an unrelated polymer class, polyethylenimines (PEIs). Alkylated PEIs attached to flat macroscopic surfaces and to those of nanoparticles make these materials highly bactericidal toward both Gram-positive and Gram-negative pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
219
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(231 citation statements)
references
References 32 publications
7
219
0
1
Order By: Relevance
“…35 The immobilization was followed by alkylation, acylation, or carboxyalkylation to generate cationic (quaternary ammonium), neutral (amide), and zwitter-ionic (quaternary ammonium carboxylic acid) functional groups, respectively. Alkylation was performed with a range of chainlengths (ethyl, Butyl, hexyl, dodecyl, and octadecyl) followed by subsequent methylation to quaternize the amine.…”
Section: Aliphatic Quaternary Ammonium Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The immobilization was followed by alkylation, acylation, or carboxyalkylation to generate cationic (quaternary ammonium), neutral (amide), and zwitter-ionic (quaternary ammonium carboxylic acid) functional groups, respectively. Alkylation was performed with a range of chainlengths (ethyl, Butyl, hexyl, dodecyl, and octadecyl) followed by subsequent methylation to quaternize the amine.…”
Section: Aliphatic Quaternary Ammonium Polymersmentioning
confidence: 99%
“…Irreversible immobilization of the antimicrobial agents in the device offers an alternative motif that eliminates patient exposure to elutable active agents and potentially increases the duration of antimicrobial efficacy. 8,9 A wide range of antimicrobial agents have been immobilized, including small molecules (e.g., quaternary ammonium silanes), [10][11][12][13][14][15][16][17] quaternary ammonium polymers, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] polyamines, [36][37][38][39][40][41][42] chitosan, [43][44][45][46][47][48][49] enzymes, [50][51][52][53][54][55] peptides, and peptide mimetics. …”
Section: Introductionmentioning
confidence: 99%
“…Helander et al demonstrated that PEI increased cell permeability to the fluorescent dye 1-Nphenylnaphthylamine (19). Several papers by Klibanov and colleagues (26,27) have shown that alkylated derivatives of PEI can exert an antimicrobial effect when incorporated into surfaces and textiles. This was proposed to occur due to the fact that the alkyl chains were long enough to penetrate from the surface to the bacterial membrane (28).…”
Section: Vol 50 2006 Photoinactivation With Pei-chlorin(e6) Conjugamentioning
confidence: 99%
“…A number of polycations possessing antimicrobial properties were developed for this purpose including ion exchange fibers [8], alkoxysilanes [9], soluble and insoluble pyridinium-type polymers [10,11], polyionenes [12], polymer surfaces derivatized with poly(vinyl-N-pyridinium) [13,14], and immobilized N-alkylated polyethyleneimine [15][16][17].…”
Section: Introductionmentioning
confidence: 99%